2012
DOI: 10.2320/matertrans.m2012102
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Plastic Deformation Behavior of Zr<sub>70</sub>Ni<sub>16</sub>Cu<sub>6</sub>Al<sub>8</sub> Bulk Metallic Glass at Cryogenic Temperature

Abstract: A hypoeutectic ZrNiCuAl bulk metallic glass (BMG) shows a clear tensile plastic deformation under a high strain rate condition at room temperature. In this study, the effect of cryogenic temperature and strain rate on the tensile plastic deformation behavior of the hypoeutectic ZrNiCuAl BMG was investigated. Tensile tests were performed for the hypoeutectic ZrNiCuAl BMG specimen with gauge part dimensions of 2.3 mm in length and 0.8 mm in diameter at cryogenic temperature (133 K) under different strain rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…By performing quasi-static and dynamic tension, Mukai et al [10] argued that the fracture strength (also yielding strength) of a Pd 40 Ni 40 P 20 BMG was essentially independent on strain rate. Similar results had also been found by other researchers at strain rate from 10 −5 s −1 to 10 −1 s −1 in Zr-based BMGs [11,12]. Based on the nanoindentation method, Bhattacharyya et al [13] presented a negative strain rate sensitivity in a Zr-based BMG.…”
Section: Introductionsupporting
confidence: 77%
“…By performing quasi-static and dynamic tension, Mukai et al [10] argued that the fracture strength (also yielding strength) of a Pd 40 Ni 40 P 20 BMG was essentially independent on strain rate. Similar results had also been found by other researchers at strain rate from 10 −5 s −1 to 10 −1 s −1 in Zr-based BMGs [11,12]. Based on the nanoindentation method, Bhattacharyya et al [13] presented a negative strain rate sensitivity in a Zr-based BMG.…”
Section: Introductionsupporting
confidence: 77%
“…(ii) As many previous studies [45,[107][108][109][110] demonstrated that metallic glasses show an excellent plasticity behavior at a cryogenic temperature, it is not known yet whether such temperature dependence of plasticity could be correlated with the secondary relaxation of metallic glasses, particularly the fast  relaxation.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Lowered temperature is generally predicted to increase strength. Several experimental studies have looked at different BMG alloys in cryogenic conditions, reporting increases in yield strength [11][12][13] and plasticity [11,12,14]. Some report the concentration of deformation into one major shear band rather than several minor ones at low temperatures and strain rates [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…The plasticity for this alloy was later improved to 2.8 % by increasing the sample cooling rate during casting, entrapping higher free volume to facilitate STZ coordination, as well as by testing at 1.5 x 10 -1 s -1 [22]. This improvement was linked to an increased ability to form multiple shear bands at high strain rates [14,22]. Low temperature and strain rate, i.e.…”
Section: Introductionmentioning
confidence: 99%